2004
DOI: 10.1051/forest:2004060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage conditions on post planting water status and performance of Pinus radiata D. Don stock-types

Abstract: -We examined the post-planting effect of storage on the plant quality and initial survival potential of bare-root (BR) and soil-plugged root (PR) of radiata pine seedlings outplanted in wet and dry soils. Seedlings were subjected to planting shock even under well-watered conditions. Although the transpiration rate declined, indicating closure of stomata, water stress occurred as evidenced by the decline in relative water content (RWC) and in the leaf water potential. More than 80% of the PR seedlings and only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…As observed previously a greater allocation to root growth improves seedling survival [8,20]. Midday RWC was also closely correlated with survival, similarly to Mena-Petite et al conclusions [29]. These results confirm that both traits can be considered reliable indicators of initial survival [13].…”
Section: Factorsupporting
confidence: 77%
“…As observed previously a greater allocation to root growth improves seedling survival [8,20]. Midday RWC was also closely correlated with survival, similarly to Mena-Petite et al conclusions [29]. These results confirm that both traits can be considered reliable indicators of initial survival [13].…”
Section: Factorsupporting
confidence: 77%
“…In previous papers we have investigated the effects of storage conditions and root coverage on the physiology of seedlings after several days' storage, focusing particularly on how this affects the seedlings' functional integrity and initial survival potential (Mena-Petite et al 2001, 2003, 2004a. Our findings showed that storage caused a decrease in seedling water status and an increase in electrolyte leakage, indicating membrane damage (Mena-Petite et al 2001).…”
Section: Introductionmentioning
confidence: 54%
“…On the other hand, evidence has been presented showing that field performance potential can be predicted more precisely using limiting environmental conditions (Folk and Grossnickle 1997). This was borne out in a later work where our results (Mena-Petite et al 2004a) showed that the transplants, even when regularly irrigated, suffered from planting shock as exhibited by decreased water potential, which remained low even after the decline of stomatal conductance. Duration of the stress depended on water content at the time of planting and on previous history of stock type (MenaPetite et al 2004a).…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations